Cover Journal of Infrastructure & Facility Asset Management - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Preliminary Recognition of River InfrastructureMahendra Andiek Maulana, Hitapriya Suprayitno & Ria Asih Aryani SoemitroReflection on Data Error Identification Methods for Field Survey Data on Commuter Train Pasengger Travel BehaviorHitapriya Suprayitno & Ria Asih Aryani SoemitroGradation Analysis of Reclaimed Asphalt Pavement from National Road as Asphalt Concrete LayerAri Widayanti, Ria Asih Aryani Soemitro, Januarti Jaya EkaPutri& Hitapriya SuprayitnoMental Tasks EEG Signal Classification Using Support Vector MachineWahyu Caesarendra, Syahara U. Lekson & Muhammad AgungSearching the Appropriate Minimum Sample Size Calculation Method for Commuter Train Passenger Travel Behavior SurveyAnita Susanti, Ria Asih Aryani Soemitro, Hitapriya Suprayitno & Vita Ratnasari